Investigation of strontium transport and strontium quantification in cortical rat bone by time-of-flight secondary ion mass spectrometry. Issue 151 (6th February 2019) - Kern, Christine; Quade, Mandy; Ray, Seemun; Thomas, Jürgen; Schumacher, Matthias; Gemming, Thomas; Gelinsky, Michael; Alt, Volker; Rohnke, Marcus
Abstract : Next-generation bone implants will be functionalized with drugs for stimulating bone growth. Modelling of drug release by such functionalized biomaterials and drug dispersion into bone can be used as predicting tool for biomaterials testing in future. Therefore, the determination of experimental parameters to describe and simulate drug release in bone is essential. Here, we focus on Sr 2+ transport and quantification in cortical rat bone. Sr 2+ dose-dependently stimulates bone-building osteoblasts and inhibits bone-resorbing osteoclasts. It should be preferentially applied in the case of bone fracture in the context of osteoporotic bone status. Transport properties of cortical rat bone were investigated by dipping experiments of bone sections in aqueous Sr 2+ solution followed by time-of-flight secondary ion mass spectrometry (ToF-SIMS) depth profiling. Data evaluation was carried out by fitting a suitable mathematical diffusion equation to the experimental data. An average diffusion coefficient of D = (1.68 ± 0.57) · 10 −13 cm 2 s −1 for healthy cortical bone was obtained. This value differed only slightly from the value of D = (4.30 ± 1.43) · 10 −13 cm 2 s −1 for osteoporotic cortical bone. Transmission electron microscopy investigations revealed a comparable nano- and ultrastructure for both types of bone status. Additionally, Sr 2+ -enriched mineralized collagen standards were prepared for ToF-SIMS quantification of Sr 2+ content. The obtained calibration curve was used for Sr 2+ quantification in cortical and trabecular bone in real bone sections. The results allow important insights regarding the Sr 2+ transport properties in healthy and osteoporotic bone and can ultimately be used to perform a simulation of drug release and mobility in bone.